General Health and Quality of Life in Patients With Sexual Dysfunctions - Naeinian, Mohammad Reza; Shaeiri, Mohammad Reza; Hosseini, Fahimeh Sadat (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> Purpose: To study the general health and quality of life in patients with sexual dysfunctions. Materials and Methods: One hundred and thirty-seven patients with diagnosis of a known sexual dysfunction (SD) were studied. A healthy group of 111 individuals matched for sex, education, and marital status were also selected as a control group. Both groups completed two questionnaires: General Health Questionnaire-28 (GHQ-28) and Personal Wellbeing Index– Adult (PWI-A). To analyze data, descriptive methods as well as student t test for independent groups were used. Results: The mean scores for individuals suffering from SD were more than the control group in total GHQ scale and all its subscales. The mean scores in total PWI-A scale and most of its subscales for individuals suffering from SD were lower than the control group. Since the obtained t values (4.16 to 5.22) for all the comparisons done between the mean scores in GHQ for the two groups were higher than t value in the ‘t table’ for df = 206 at α = 0.01 (2.58), differences obtained were significant. Since obtained t values (-2.03 to 4.65) for total quality of life and health, achievements, personal relationship, safety, and feeling part of community dimensions were higher than t value in the ‘t table’ for df = 206 at α = 0.05 and α = 0.01 (1.96 and 2.58, respectively), differences obtained except for standard of living and future security were significant. Conclusion: Somatic, social, and mental measures for people having sexual dysfunctions (patient group) were lower than the control group.